2017
DOI: 10.1080/1828051x.2017.1415703
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antimicrobial resistance patterns and dominance of extended spectrum β-lactamase genes among faecal Escherichia coli isolates from broilers and workers during two rearing periods

Abstract: The emergence of antibiotic-resistant Escherichia coli, especially extended-spectrum b-lactamase (ESBL)-producing strains, in the intestinal tract of broilers could be a threat to poultry and human. We investigated changes of antimicrobial resistance patterns and frequency of ESBL genes among faecal E. coli isolates of broilers and workers in five different farms during two rearing periods in Iran. In this regard, E. coli was isolated from rectal swabs of the workers and cloacal swabs of the broilers. After de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(27 reference statements)
0
2
1
Order By: Relevance
“…In contrast, resistance to meropenem was the lowest and this may be due to non-use of the carbapenemase class of antibiotics for therapy in poultry. Geographically, this result contrasts that of [26] that the percentage resistance of E. coli from human origin to carbapenemese in most European countries was less than 1% [27]. Majority of the isolates were resistant to multiple classes of antibiotics.…”
Section: Resultscontrasting
confidence: 79%
“…In contrast, resistance to meropenem was the lowest and this may be due to non-use of the carbapenemase class of antibiotics for therapy in poultry. Geographically, this result contrasts that of [26] that the percentage resistance of E. coli from human origin to carbapenemese in most European countries was less than 1% [27]. Majority of the isolates were resistant to multiple classes of antibiotics.…”
Section: Resultscontrasting
confidence: 79%
“…There is great variation in the prevalence of ESBL producing E. coli in broiler farms from different countries. For example, ESBL farm prevalence was reported in 28.21% of boot swab samples and, 60.26% by cloacal swab samples in the Philippines, 45 % from Belgium, 100% from Netherlands, 6.3% from Iran, and 42.1% from Portugal (Costa et al, 2009;Dierikx et al, 2013;Doregiraee et al, 2018;Gundran et al, 2019;Huijbers et al, 2014;Smet et al, 2008). These differences may be due to differences in locations, time, sampling strategy, and laboratory techniques (Li et al, 2016;Gundran et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, [22] reported that the percentage resistance of E. coli from human origin to carbapenemase in most European countries was less than 1% except Belaraus, with a higher range of 10% -25%. Also, the level of resistance of E. coli from poultry and human sources in Iran to meropenem was reported to be 20% and 60%, respectively [23].…”
Section: Table 1 Types Of Antibiotics/antimicrobials Administered Onmentioning
confidence: 99%